Corrosion of sedimentary liquids on internal bottom plate of tanks among coal liquefaction process. Issue 4 (9th August 2018) - Lu, Yawei; Wang, Zhirong; Jiang, Juncheng; Dou, Zhan; Xue, Anxue; Wang, Jian
Abstract : The leakage accidents due to the corrosion on the internal bottom plates occurred frequently in the tanks which are involved in the first commercial direct coal liquefaction production line. For comprehending the corrosion, the compositions of the sedimentary liquids from diesel, hydro‐upgrading feed oil, heavy solvent oil, thick condensed oil and hydro‐stabilizing feed oil are surveyed in the first place, the results show that all the sedimentary liquids are almost neutral; the cations and anions in all sedimentary liquids are the same; the majority of ions are Ca 2+, Cl −, and SO 4 2 − in these five sedimentary liquids. Then the immersion and electrochemical tests are implemented, it is represented that corrosion of same sedimentary liquid on Q235 steel coupon is severer than that on 16MnR steel coupon; the sedimentary liquid from hydro‐stabilizing feed oil has the most violent causticity; all the corrosives may hold the Fe2 CO3 and Fe2 O3 ; the polarization behavior of Q235 steel in the sedimentary liquid from hydro‐stabilizing feed oil is similar to that of 16MnR steel. Finally, the influences of different ions on the corrosivity of sedimentary liquids are also investigated, it can be concluded that the 672‐h general corrosion rates of Q235 and 16MnR steel coupons in all sedimentary liquids increase with improve of Cl‐ content but decrease with rising of SO 4 2 − content; in the sedimentary liquids containing large numbers of Cl ‐ and Ca 2+, the Ca 2+ is the definitely vital ion which deeply influences the corrosivity of sedimentary liquids. The achievement of this research work also can be applied in the prevention for corrosion formed on the internal bottom plates of tanks referred to the direct coal liquefaction process. © 2018 American Institute of Chemical Engineers Process Saf Prog 37: 506–517, 2018